2016
DOI: 10.1016/j.dadm.2016.05.004
|View full text |Cite
|
Sign up to set email alerts
|

MCP‐1 and eotaxin‐1 selectively and negatively associate with memory in MCI and Alzheimer's disease dementia phenotypes

Abstract: IntroductionMCP-1 and eotaxin-1 are encoded on chromosome 17 and have been shown to reduce hippocampal neurogenesis in mice. We investigated whether these chemokines selectively associate with memory in individuals with mild cognitive impairment (MCI) and Alzheimer's disease (AD) dementia.MethodsMCP-1 and eotaxin-1 were assayed in controls, MCI, and AD dementia patients with varying phenotypes (n = 171). A subset of 55 individuals had magnetic resonance imaging (MRI) scans available. Composite scores for cogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 33 publications
4
49
0
Order By: Relevance
“…Senescence‐associated secretory phenotype can promote secondary senescence in healthy cells (Coppe, Desprez, Krtolica & Campisi, ), and senescent cells have been demonstrated to promote aging and age‐related disease (Baker et al., , ; Zhu et al., ). Circulating levels of MCP‐1 are increased in patients with renal disease (Akdogan et al., ), cognitive impairment and Alzheimer's disease (Bettcher et al., ), atherosclerosis and cardiovascular disease (Deo et al., ). Monocyte chemoattractant protein‐1 is considered to be a marker of “inflammaging,” defined as chronic sterile inflammation that is associated with numerous age‐related diseases (Franceschi & Campisi, ).…”
Section: Resultsmentioning
confidence: 99%
“…Senescence‐associated secretory phenotype can promote secondary senescence in healthy cells (Coppe, Desprez, Krtolica & Campisi, ), and senescent cells have been demonstrated to promote aging and age‐related disease (Baker et al., , ; Zhu et al., ). Circulating levels of MCP‐1 are increased in patients with renal disease (Akdogan et al., ), cognitive impairment and Alzheimer's disease (Bettcher et al., ), atherosclerosis and cardiovascular disease (Deo et al., ). Monocyte chemoattractant protein‐1 is considered to be a marker of “inflammaging,” defined as chronic sterile inflammation that is associated with numerous age‐related diseases (Franceschi & Campisi, ).…”
Section: Resultsmentioning
confidence: 99%
“…The relationship between measures of cognition and CCL11 has not been widely explored. Small studies in patients diagnosed with MCI or AD have generated mixed findings (Bettcher et al, 2016;Leung et al, 2013;Westin et al, 2012). Bettcher et al found that higher levels of CCL11 in combination with MCP-1 predict worse memory functions in MCI and AD phenotypes (Bettcher et al, 2016), whereas Leung and co-workers reported significantly higher levels of CCL11 in patients with AD compared to those with MCI (Leung et al, 2013).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…More recently, circulating levels of CCL11 have been shown to rise with normal human ageing (Bradburn et al;Shurin et al, 2007;Villeda et al, 2011) and in neurodegenerative diseases (Huber et al, 2018). In particular, small studies have linked higher blood levels of CCL11 with Alzheimer's disease (AD) (Choi et al, 2008) and with memory deficits in older adults diagnosed with mild cognitive impairment (MCI) and AD dementia phenotypes (Bettcher et al, 2016). In contrast, high CCL11 levels were found to correlate with a delayed age at onset in AD (Lalli et al, 2015) suggesting a complex role of this chemokine in neurodegeneration.…”
Section: Introductionmentioning
confidence: 99%
“…In this issue, Bettcher et al. [9] study MCP‐1 and eotaxin‐1 levels among controls, MCI, and AD cases in relation to memory abilities as well as medial temporal lobe volumes. When both chemokines were elevated, memory scores were specifically poorer.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Recent work has begun to study the link between biomarker levels and specific clinically relevant outcomes (e.g., memory scores, structural MRI outcomes) [8]. In this issue, Bettcher et al [9] study MCP-1 and eotaxin-1 levels among controls, MCI, and AD cases in relation to memory abilities as well as medial temporal lobe volumes. When both chemokines were elevated, memory scores were specifically poorer.…”
Section: Identifying Endophentoypes Within Admentioning
confidence: 99%